C. Jordán Cólera, Celtibérico (Monografías de Filología Griega 16), Zaragoza, Universidad, 2004, IV + 476 págs. ISBN: 84-96214-38-9 (Minerva. Revista de Filología Clásica, 2019)
Reseña de C. Jordán Cólera, Celtibérico (Monografías de Filología Griega 16), Zaragoza, Universidad, 2004, IV + 476 págs. ISBN: 84-96214-38-9